Road to recovery - Tan, Jiayi (2017)
Road to Recovery is a short 3D animation film by Tan Jiayi. It is about a bird’s journey to the start of his recovery from his past, exploring themes of self-harm, acceptance and receiving help. This report details the idea and concept of the film, along with its preproduction, production, postproduction stages of making the flim. Software used for this project includes Maya, Adobe Photoshop and Adobe Premiere Pro.